High-density Lipoprotein Cholesterol as a Risk Factor of Health-Related Quality of Life in 50–70-Year-Old Community-Dwelling Women - Wratsangka, Raditya; Herwana, Elly; Yenny, Yenny; Xavieress, Endrico; Krishnamurti, Aditya (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The prevalence of dyslipidemia, a risk factor of cardiovascular disease, is at present sufficiently high, particularly in the elderly. Health-related quality of life (HRQoL) is also an important outcome in the treatment of dyslipidemia, which is currently more targeted at lowering the low-density lipoprotein cholesterol (LDL-C) concentration. AIM: The aim of this study was to determine the relationship between the high-density lipoprotein cholesterol (HDL-C) concentration and HRQoL in community-dwelling women aged 50–70 years. METHODS: A cross-sectional study involving 137 women aged 50–70 years who underwent blood sampling for determining the concentrations of hemoglobin, total cholesterol (TC), LDL-C, and HDL-C. A questionnaire was given to all subjects regarding data on age, menopausal status, level of education, and also another questionnaire of SF-36 for evaluation HRQoL. Bivariate and multivariate logistic regression analysis was used to identify risk factors associated with HRQoL. RESULTS: In bivariate logistic regression analysis, age, menopausal status, education level, anemia, TC, and LDL-C were found to have non-statistically significant association with HRQoL, but HDL-C was significantly associated with HRQoL (odds ratio = 0.44; 95% Confidence interval [CI] = 0.20–0.97; p = 0.042). In multivariate analysis, menopausal status and education level have a non-statistically significant association with HRQoL, but those normal level of HDL cholesterol was found 0.18 times less likely to be associated with poor HRQoL (Adjusted odds ratio 0.18; 95% CI = 0.03–0.91; p = 0.038). CONCLUSION: This study showed that HDL-C levels were risk factors of HRQoL in women 50–70 years of age.